Chewing tar in the early Holocene : an archaeological and ethnographic evaluation - Aveling, E.M
Introduction \Amorphous lumps of putative tar with human tooth impressions have been recovered from several prehistoric sites in Scandinavia (e.g. Bang-Andersen 1976; Larsson 1982; Johansson 1990; Regnell et al. 1995; Hernek & Nordqvist 1995), southern Germany (Rottlander 1981, Schlichtherle and Wahlster 1986, Alexandersen 1989) and Switzerland (Schoch 1995). The term 'tar' is used here to refer to a product of the destructive heating of wood, bark or resin. Although small in number, these finds date to the Mesolithic and Neolithic periods and can be described as hardened lumps or shapeless masses, brown to black in colour, with distinctive tooth impressions. Similar, although apparently unchewed lumps of tar have also been recovered (e.g. Clark 1954: 167; Larsson 1983: 75; Binder et al. 1980; Cattani 1993). Although mentioned briefly in site reports, the scarcity of such finds combined with the difficulty in identifying amorphous samples of organic matter